Hazen-Williams Pipe Flow Calculations - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2019)
This Excel workbook conveniently makes calculations for pressure flow of water through pipes. There are four worksheets. One calculates the water flow rate for specified pipe diameter and length, Hazen-Williams coefficient, head loss, and sum of minor loss equivalent pipe lengths. The second calculates the required pipe diameter for specified water flow rate, pipe length, Hazen-Williams coefficient, head loss and sum of minor loss equivalent pipe lengths. The third calculates the pressure drop for sprecified water flow rate, pipe diameter and length, Hazen-Williams coefficient, and sum of minor loss equivalent pipe lengths. The fourth worksheet calculates the pipe length for specified water flow rate, pipe diameter, head loss, Hazen-Williams coefficient, and sum of minor loss equivalent pipe lengths.